Multicentre, prospective, randomised, open-label, blinded end point trial of the efficacy of allopurinol therapy in improving cardiovascular outcomes in patients with ischaemic heart disease: protocol of the ALL-HEART study - Mackenzie, Isla S.; Ford, Ian; Walker, Andrew; Hawkey, Chris; Begg, Alan; Avery, Anthony; Taggar, Jaspal; Wei, Li; Struthers, Allan D.; MacDonald, Thomas M. (BMJ Publishing Group, 2016)
Introduction